The effects of ochratoxin/aluminosilicate interaction on the tissues and humoral immune response of broilers - Santin, E.; Paulillo, A. C.; Maiorka, P. C.; Alessi, A. C.; Krabbe, E. L.; Maiorka, A. (Carfax Publishing, 2002)
This study aimed to evaluate the effect of dietary ochratoxin, in the presence or absence of aluminosilicate, on the histology of the bursa of Fabricius, liver and kidneys, and on the humoral immune response of broilers vaccinated against Newcastle disease virus. The exposure of birds to 2 p. p. m. ochratoxin, in the presence or absence of aluminosilicate, reduced their humoral immune response and the number of mitotic cells in the bursa. The relative weight of the livers of the birds exposed to this toxin was increased and, microscopically, there was hepatocyte vacuolation and megalocytosis with accompanying hyperplasia of the biliary epithelium. The kidneys showed hypertrophy of the renal proximal tubular epithelium, with thickening of the glomerular basement membrane. Aluminosilicate did not ameliorate the deleterious effects of the ochratoxin.